Childhood and Markets Infants, Parents and the Business of Child Caring - Martens, Lydia (Studies in Childhood and Youth, 2018)
This book explores how young children and new families are located in the consumer world of affluent societies. The author assesses the way in which the value of infants and monetary value in markets are realized together, and examines how the meanings of childhood are enacted in the practices, narratives and materialities of contemporary markets. These meanings formulate what is important in the care of young children, creating moralities that impact not only on new parents, but also circumscribe the possibilities for monetary value creation. Three main understandings of early childhood - those of love, protection and purification - and their interrelationships are covered, and illustrated with examples including food, feeding tools, nappies, travel systems and toys. The book concludes by re-examining the relationship between adulthood and the cultural value of young children, and by discussing the implications of the ways markets address young children, also examines the realities of older children in consumer culture. Childhood and Markets will be of interest to students and scholars of sociology, childhood studies, anthropology, cultural studies, media studies, business studies and marketing.